Internet of Things Architecture and Applications : A Overview - Pradhan, Kiran M; Kasbe, Suchitra K; Pradhan, Vaishnavi M (International Journal of Computer Sciences and Engineering, 2025)
Internet of Things (IoT) refers to objects that have unique identities and are connected to the internet. While many existing devices, such as networked computers or 4G-enabled mobile phones, already have some form of unique identities and are also connected to internet. Internet of Things is a new revolution of the internet that is rapidly gathering momentum driven by the advancement in sensor networks, mobile devices, wireless communications, networking and cloud technologies. Experts forecast that in future there will be all devices/ things connected to internet. The aim of the Internet of Things (IoT) is to enable things to be connected anytime, anyplace with anything. The IoT is comprised of smart machines interacting and communicating with other machines, environments and infrastructures. As a result, huge volumes of data are being generated, and that data is being processed into useful actions that can make our lives much easier and safer and to reduce our impact on the environment. Internet of Things architecture is capable enough to improve the understanding of related tool, technology, and methodology to facilitate developer’s requirements. Various applications of IoT have been developed and researchers of IoT identified the opportunities and challenges used in IoT such as sensors, actuators, mobile phones. In this paper we discussed IoT, its architecture, and applications of IoT. The creativity of this new era is unlimited, with amazing potential to improve our lives. The following paper is an extensive reference to the utility, applications and an evolution of the Internet of Things